DEVELOPMENT OF DECISION SUPPORT SYSTEM APPLICATION FOR ADMISSION OF NEW STUDENTS AND DETERMINATION OF MAJOR USING SIMPLE ADDITIVE WEIGHTING (SAW) - Ramadaniah, Dedeh; Nurjannah, Kartika Sari; Romahdoni, Muhammad Reza; Andrew, Joseph (Universitas Islam Negeri Raden Intan Lampung, 2022)
The process of accepting new students at Taman-Siswa of Senior High School has so been manual namely, prospective students register with a writer on the registration form. So recapitulated by new student committee into the computer. In the process of recapitulating only Microsoft Office was for managing and haven't used an information system so need a long time and was found less effective. A Decision Support System (SPK) is an interactive information system interactive that provides information, modelling and data manipulation. This system is used to assist decision-making in semi-structured and unstructured situations. The SAW method is often also known as the weighted sum method. The basic concept of the SAW method is to find the weighted sum of the performance ratings for each alternative on all attributes. The Decision Support System uses the SAW (Simple Additive Weighting) method. used to provide recommendations to students to choose majors. The result of the system calculation is the ranking of the scores for Mathematics Report Cards, Indonesian Language Report Scores, English Report Scores, Science Report Scores, IPS Report Scores, Science Interests, Social Science Interests, Science Parents' Advice, IPS Parents' Advice wished for next developing in information system It has interactive facilities based on Android which can be installed on the smartphones of all concerned users. Information system websites for acceptance and determination of majors would be better if facilitated by an SMS Gateway to remind online test schedules.